Effect of Integrated Management System of ISO 9001:2015 and ISO 22000:2018 Implementation To Packaging Industries Quality Performance at Banten Indonesia - Purwanto, Agus; Asbari, Masduki; Santoso, Priyono Budi (2020)
The purpose of this study was to determine the effect of the implementation of the integrated management system to Quality Performance. This research was conducted in several packaging industrial in the province of Banten, The respondents were 144 employees from 12 companies of packaging industry which have implemented the Integration Management System for at least five years. The background of the study is due to the lack of research on the ISO 9001: 2015 and ISO 22000: 2018. The data was collected by distributing questionnaires and analysis of data using the Structural Equation Model (SEM) using a Linear Structural Model (LISREL) version 8.70. The results showed that the application of Integration Management System ISO 9001: 2015 and ISO 22000: 2018 a significant influence to quality performance such as increased customer satisfaction index, customer complaint reduction, reduction of defects, decrease product returns and reduced cost of quality.